Strength basics your guide to resistance training for health and optimal performance - Cook, Brian B.; Stewart, Gordon W. (Human Kinetics, 1996)
If you're looking for better fitness or better sports performance, success starts with Strength Basics. This easy-to-understand guide explains resistance-training fundamentals and shows you how to design a strength-training program using common types of equipment and body-weight exercises. Written for beginning and less experienced strength trainers who want to make sure they're on the right track, the book provides practical, how-to advice for safe and effective workouts to do at home or at the gym. Inside you'll find 66 exercises to make you stronger, plus 16 ready-to-use sport-specific programs designed to meet the demands of your favorite sports activities.